Narrative Review Comparing Principles and Instruments Used in Three Active Surveillance and Control Programmes for Non-EU-regulated Diseases in the Danish Cattle Population - Nielsen, Liza Rosenbaum; Houe, Hans; Nielsen, Søren Saxmose (Frontiers in Veterinary Science, 2021)
The objective of this paper is to provide a comparative review of three active surveillance and control programmes in the Danish cattle sector to highlight important differences for decision makers to develop successful programmes. The focus is on differences in purpose, principles, design and instruments applied to achieve the goals stated for each programme for bovine viral diarrhoea (BVDV), paratuberculosis and Salmonella Dublin. The purposes of the programmes are to reduce economic consequences and improve animal welfare, and for S. Dublin also to prevent zoonotic risk, with varying importance as motivation for the programmes over time. The targets of the BVDV and S. Dublin programmes have been to eradicate the diseases from the Danish cattle population. This goal was successfully reached for BVDV in 2006 where the programme was changed to a surveillance programme after 12 years with an active control programme. The S. Dublin dairy herd-level prevalence decreased from 25% in 2003 to 6% in 2015, just before the milk quota system was abandoned. Over the last 5 years, the prevalence has increased to 8-9% test-positive dairy herds. It is mandatory to participate, and frequent updates of legislative orders were used over two decades as critical instruments in those two programmes. In contrast, participation in the paratuberculosis programme is voluntary and the goals are to promote participation and reduce the prevalence and economic and welfare consequences of the disease. The daily administration of all three programmes is carried out by the major farmers’ organisation, who organise surveillance, IT-solutions and other control tools, projects and communication in collaboration with researchers from the universities, laboratories and, for BVDV and S. Dublin, the veterinary authorities. Differences among the programme designs and instruments are mainly due to the environmental component of paratuberculosis and S. Dublin, as the bacteria able to survive for extended periods outside the host. This extra diffuse source of infection increases the demand for persistent and daily hygiene and management efforts. The lower test sensitivities (than for BVDV) lead to a requirement to perform repeated testing of herds and animals over longer time periods calling for withstanding motivation among farmers.